Nutritional Status and Macronutrient Adequacy Are Associated with Increased Odds of PCOS in Women of Reproductive Age: A Case-Control Study - Rohmah, Auliatur; Dini, Cleonara Yanuar (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
Polycystic ovary syndrome (PCOS) is a reproductive endocrinological disorder that has been linked to nutritional status and macronutrient adequacy. PCOS affects between 12%-21% of women of reproductive age. This study aimed to analyze the associations between nutritional status and macronutrient adequacy (carbohydrates, fats, and proteins) and the odds of PCOS among women of reproductive age. This case-control study was conducted on 196 women aged 15-49 years (48 case-group women with PCOS and 148 control-group healthy women). Macronutrient adequacy was assessed using the Semi-Quantitative Food Frequency Questionnaire over the last three months, and nutrition status was assessed using anthropometric measurements. In the case group, 60.4% of women were overweight, with excess carbohydrate and fat adequacy observed in 58.3% and 72.9%, respectively, while 43.8% had adequate protein. This study showed that overweight and obese (p = 0.000; OR = 2.95), carbohydrate adequacy (p = 0.001; OR = 3.87), and fat adequacy (p = 0.001; OR = 3.22) were significantly associated with PCOS, whereas protein adequacy (p = 0.060; OR = 0.96) was not. After adjustment for potential confounders using the Chi-Square test, protein adequacy remained non-significant. Nutritional status and macronutrient adequacy were associated with increased odds of PCOS among women of reproductive age.